IMPROVING STUDENT LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING MODEL ON THE THEME OF THE BEAUTY OF MY COUNTRY'S DIVERSITY IN CLASS IV OF SD IT KHAIRUL FATAYA - Aryana, Nisa; Nurmairina, Nurmairina (Media Inovasi Pendidikan dan Publikasi, 2024)
The research conducted in class IV of SD IT Khayrul Fataya aims to improve student learning outcomes through the Cooperative Learning learning model. The action was carried out in two cycles, and each cycle consisted of two meetings. The research instruments used in this study include: student activity observation sheets and teacher activity observation sheets. The data generated were then analyzed to determine the results obtained in each cycle and to determine the development of each action given. Based on the results of observations of student learning outcomes in cycle I, there was 1 student who got a very high score, 2 students who got a high score, 1 student who got a sufficient score, 6 students who got a low score. It can be concluded that 4 students completed the initial test and 6 students did not complete the initial test. Student activities in cycle 1, the teacher has taught according to the steps of the direct learning model (Direct Instruction). The percentage of thematic learning achievement using the direct learning model (Direct Instruction) got a percentage of 80% obtained from the results of observations of student activities. Based on the results of observations of student learning outcomes in cycle I, there was 1 student who got a very high score, 2 students who got a very high score, 3 students who got a high score, 4 students who got a sufficient score and 1 student who got a very low score. It can be concluded that 9 students completed the cycle II test and 1 student did not complete the cycle II test. Student learning activities in implementing learning in cycle II. The percentage of thematic learning achievement using the cooperative learning model and using learning videos can be categorized as very good, this can be proven in attachment 2 of the student observation sheet for cycle II is 93%. Based on the results of teacher observations of the researcher's ability to implement learning in cycle II. The percentage of thematic learning achievement using the cooperative learning model and using learning videos can be categorized as very good, this can be proven in the attachment of the results of the teacher observation sheet for cycle II is 100%.